Left Atrial to Femoral Artery Full Cardiopulmonary Bypass: A Novel Technique for Descending and Thoracoabdominal Aortic Surgery - Papanikolaou, Dimitra; Savio, Chris; Zafar, Mohammad A.; Freudzon, Leon; Wu, Jinlin; Abdelbaky, Mohamed; Pelletier, Keith J.; Buntin, Joelle; Faggion Vinholo, Thais; Ziganshin, Bulat A.; Schwartz, Brian; Elefteriades, John A. (International Journal of Angiology, 2020)
Left atrial-femoral artery (LA-FA) bypass with a centrifugal pump and no oxygenator is commonly used for descending and thoracoabdominal aortic (DTAA) operations, mitigating the deleterious effects of cross-clamping. We present our initial experience performing DTAA replacement under LA-FA (left-to-left) cardiopulmonary bypass (CPB) with an oxygenator. DTAA replacement under LA-FA bypass with an oxygenator was performed in 14 consecutive patients (CPB group). The pulmonary vein and femoral artery (or distal aorta) were cannulated and the full CPB machine were used, including oxygenator, roller pump, pump suckers, and kinetically enhanced drainage. The CPB group was compared with 50 consecutive patients who underwent DTAA replacement utilizing traditional LA-FA bypass without an oxygenator (LA-FA group). Perioperative data were collected and statistical analyses were performed. All CPB patients maintained superb cardiopulmonary stability. The pump sucker permitted immediate salvage and return of shed blood. Superb oxygenation was maintained at all times. High-dose full CPB heparin was reversed without difficulty. The CPB group required markedly fewer blood transfusions than the LA-FA group (2.21 vs. 5.88 units, p < 0.004). The 30-day mortality rate was 7.1% (n = 1) and there were no paraplegia cases in the CPB group versus 7 (14%) deaths and 3 (6%) paraplegia cases in the LA-FA group. Traditional LA-FA bypass without an oxygenator avoids high-dose heparin. In the present era, heparin reversal is more secure. Our experience finds that the novel application of LA-FA CPB with an oxygenator is safe and suggests improved hemodynamics (immediate return of shed blood) and a hemostatic advantage (avoidance of loss of coagulation factors in the cell saver).
Keywords: descending aortic replacement; thoracoabdominal aortic replacement; cardiopulmonary bypass; left atrial-femoral bypass; aortic surgery; aortic aneurysm